2021
DOI: 10.3390/cancers13215351
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the Levels of Cellular NF-κB Activation States

Abstract: The NF-κB signaling system plays an important regulatory role in the control of many biological processes. The activities of NF-κB signaling networks and the expression of their target genes are frequently elevated in pathophysiological situations including inflammation, infection, and cancer. In these conditions, the outcome of NF-κB activity can vary according to (i) differential activation states, (ii) the pattern of genomic recruitment of the NF-κB subunits, and (iii) cellular heterogeneity. Additionally, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 123 publications
0
9
0
1
Order By: Relevance
“…The reason is that direct activity assays of these types are rather difficult to perform in vivo or in tissue homogenates. Nevertheless, there is ample information that the 65kD subunit of NF-κB functions as a potent transcriptional activator and a target for v-Rel-mediated repression [ 75 ], and therefore, if this subunit is lower, it is likely that the NF-κB system’s activity is also likely suppressed. Likewise, although the quantification of phosphorylated ERKs and ERK1/2 ratios is more common than the quantification of ERK1/ERK2 ratios, a direct relationship between the ratio of phosphorylated ERKs and the quantitative expression ratio of ERKs has been previously shown [ 76 ]; therefore, the ratio measured here may well give some indication regarding the activity of this pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The reason is that direct activity assays of these types are rather difficult to perform in vivo or in tissue homogenates. Nevertheless, there is ample information that the 65kD subunit of NF-κB functions as a potent transcriptional activator and a target for v-Rel-mediated repression [ 75 ], and therefore, if this subunit is lower, it is likely that the NF-κB system’s activity is also likely suppressed. Likewise, although the quantification of phosphorylated ERKs and ERK1/2 ratios is more common than the quantification of ERK1/ERK2 ratios, a direct relationship between the ratio of phosphorylated ERKs and the quantitative expression ratio of ERKs has been previously shown [ 76 ]; therefore, the ratio measured here may well give some indication regarding the activity of this pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of the NF-κB signaling pathway promotes the expression of its downstream inflammation-related genes ( 33 , 34 ). It has been reported that NF-κB pathway activation induces the production of NLRP3, which in turn triggers the recruitment of the bridging protein ASC and caspase-1 to form a macromolecular complex in which caspase-1 is activated.…”
Section: Discussionunclassified
“…However, some studies in vivo showed that the increased NF-κB activity in macrophages resulted in reduced tumor burden and persistent macrophage M1 polarization [ 165 ]. There are five members of the NF-κB family of transcription factors: p65 (RELA), p50 (NFKB1), p52 (NFKB2), c-REL, and RELB [ 166 ]. These members can couple to form different homo- or heterodimers, which have opposing effects on macrophage polarization, depending on the source of macrophage populations and the way that macrophages are activated [ 167 ].…”
Section: Hypoxia-driven Crosstalk Between Tumor Cells and Tamsmentioning
confidence: 99%